2015
DOI: 10.5796/electrochemistry.83.701
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Reactions of Intercalation Electrodes in Lithium Ion Batteries

Abstract: Gaining a thorough understanding of the electrochemical interface in lithium ion batteries is essential for the development of a common strategy for the material design. This comprehensive paper presents the interfacial reaction analyses between intercalation electrodes and organic electrolytes using an epitaxial-film model electrode and in situ surface scattering techniques. The crystal structures of the intercalation electrodes drastically change in 10 nm-regions from the top of the electrode surface when so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Rao et al reported the preparation of well-crystallized LMO films at a high substrate temperature of T s = 700 • C and P O 2 = 13 Pa that delivered a capacity of 133 mC·cm −2 ·µm −1 at a very slow C/100 rate [144]. Several workers reported the evolution of the thin-film electrode/electrolyte interface, as the planar form of the film is the ideal geometry for such investigations [145][146][147][148]. Room temperature impedance measurements were carried out to identify the formation of the solid electrolyte interface (SEI) layer on a PLD LMO film cathode and the degradation mechanism during cycling in an aprotic electrolyte containing LiPF 6 salt.…”
Section: Limn 2 O 4 (Lmo)mentioning
confidence: 99%
See 1 more Smart Citation
“…Rao et al reported the preparation of well-crystallized LMO films at a high substrate temperature of T s = 700 • C and P O 2 = 13 Pa that delivered a capacity of 133 mC·cm −2 ·µm −1 at a very slow C/100 rate [144]. Several workers reported the evolution of the thin-film electrode/electrolyte interface, as the planar form of the film is the ideal geometry for such investigations [145][146][147][148]. Room temperature impedance measurements were carried out to identify the formation of the solid electrolyte interface (SEI) layer on a PLD LMO film cathode and the degradation mechanism during cycling in an aprotic electrolyte containing LiPF 6 salt.…”
Section: Limn 2 O 4 (Lmo)mentioning
confidence: 99%
“…A reversible disproportionation reaction was suggested with the formation of the Li 2 Mn 2 O 4 and λ-MnO 2 phases at the surface [146]. Using epitaxial-film model electrodes, Hirayama studied the surface reaction and the formation of the SEI layer and the interfacial structural reconstruction during an initial battery process using in situ surface X-ray diffraction and reflectometry [147]. TEM images confirmed the surface reconstruction that occurred during the first charge, i.e., when a potential was applied.…”
Section: Limn 2 O 4 (Lmo)mentioning
confidence: 99%
“…The electrode/electrolyte interface is a complicated reaction zone where a multitude of processes such as adsorption of solvated lithium onto the electrode surface, de-solvation, surface diffusion, charge-transfer and decomposition of electrolyte species at the surface of the electrode, [38] can occur. Importantly, electrolyte degradation has been known to influence the cycling stability of cathode materials.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of spinel compounds, it was noted that films oriented along the < 111 > direction selectively formed an SEI layer at the surface promoting growth of a thin stable SEI during cycling. [29,38,42] For layered rock salt compounds such as LiNi 0:8 Co 0:2 O 2 [43] and LiCoO 2 [41] the (110) plane was found to undergo an atomic rearrangement at the surface as a consequence of the initial electrolyte exposure, resulting in the formation of a structure optimized for the formation of a stable SEI. In the case of lithium-rich layered rocksalts, such as Li 2 RuO 3 , the an-isotropic formation of highly resistive surface layers limited the high rate intercalation of Li to the (001) planes of the structure.…”
Section: Resultsmentioning
confidence: 99%
“…Developing cathode materials with high input–output power characteristics is a critical challenge in adopting lithium‐ion battery technology for electric vehicles and plug‐in hybrid electric vehicles. [ 1,2 ] Generally, the reaction potentials and current densities of lithium deintercalation and intercalation determine power characteristics. The reaction potential is intrinsically related to the change in Gibbs energy of the cathode material and kinetical changes depending on the charge and mass transfer resistances of the lithium (de)intercalation.…”
Section: Introductionmentioning
confidence: 99%